2021
DOI: 10.47895/amp.vi0.3574
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices on HIV/AIDS among College Students in Pampanga, Philippines

Abstract: Introduction.Young adults are more susceptible to HIV infection due to a lack of reliable and timely information about HIV/AIDS prevention and transmission. This study examined the KAPS of college students in Pampanga, Philippines due to high cases of HIV in the region. KAPs is vital in developing effective strategies for HIV intervention.Objective. The study evaluated the knowledge, attitudes, and practices on prevention and transmission HIV/AIDS among college students in Pampanga, Philippines.Method. This cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
1
1
Order By: Relevance
“…Most of the studied nurses agree that AIDS patients have the same right to quality of care and respect (Table 2). These results are in agreement with James et al, (2018) (35) who stated that .most participants reported a positive attitude toward people living with HIV. Also, the present study results are in agreement with Boakye, et al, (2019) (36) who study the determinants of knowledge, attitude, and practices of Ghanaian nurses towards persons living with HIV and AIDS in Kumasi and showed that the nurses have positive attitudes, with the majority showing greater agreement with positive statements, and more disagreement with negative statements about people living with HIV.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the studied nurses agree that AIDS patients have the same right to quality of care and respect (Table 2). These results are in agreement with James et al, (2018) (35) who stated that .most participants reported a positive attitude toward people living with HIV. Also, the present study results are in agreement with Boakye, et al, (2019) (36) who study the determinants of knowledge, attitude, and practices of Ghanaian nurses towards persons living with HIV and AIDS in Kumasi and showed that the nurses have positive attitudes, with the majority showing greater agreement with positive statements, and more disagreement with negative statements about people living with HIV.…”
Section: Discussionsupporting
confidence: 92%
“…This study reveals that a significant portion of the respondents falls under the category of having low knowledge, while the majority hold moderate knowledge. This contrasts with other research, wherein 239 adolescents (42.5%) exhibited moderate knowledge, and 203 adolescents (36.1%) had high knowledge (James et al, 2022 ). Similarly, another study found that less than half of the adolescents (44.7%) demonstrated sound knowledge of HIV prevention, while 55.3% exhibited insufficient knowledge (Shamu et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 63%
“…The knowledge on HIV transmission was developed by James et al ( 2022 ), with a validity test value of 0.563 to 0.757 and a Cronbach Alpha reliability value of 0.885. This questionnaire contains 13 items measured by the Guttman scale, consisting of Yes and No answers.…”
Section: Methodsmentioning
confidence: 99%